Netnography : redefined - Kozinets, Robert V., 1964- (Los Angeles : Sage, 2015)
The new edition has been expanded to include: detailed guidance for researchers on how to combine online and in-person ethnographic methods to fully explore a social phenomenon, more focus on specific kinds of social media data from sites such as Facebook and Twitter, more specific examples of how netnography can be used in different social science fields, such as media studies, sociology, anthropology, nursing, and education, a discussion of the ways in which communal and cultural social identities are constantly being transformed by combinations of traditional and social media.
Networked sociality -- Researching networked sociality -- Netnography redefined -- Planning and preparation -- Ethics -- Data collection -- Researcher participation in data collection and creation -- Data analysis and interpretation -- Representation -- Humanist netnography.
Subtitle varies.
First edition: 2010.
Includes bibliographical references (pages 279-296) and index.
Keywords: Ethnology -- Computer network resources; Ethnology -- Research -- Computer network resources